Analiza faktora koji utiču na težinu nakon barijatrijske-metabolske operacije u bolesnika sindromu obesitosti hipoventilacije na osnovu gastrointestinalnih peptida hormona - Zhang, Jingjing; Apaer, Shadike; Zhang, Shuo; Liang, Guanyou; Li, Tao; Cao, Xinling (Journal of Medical Biochemistry, 2025)
Background: Obesity is becoming increasingly prevalent in modern society, leading to a rise in the incidence of obesity hypoventilation syndrome (OHS). This study analyzes the factors influencing weight regain in OHS patients following laparoscopic sleeve gastrectomy (LSG), based on gastrointestinal peptide hormones.Methods: A total of 134 OHS patients who underwent LSG at our hospital between January 2023 and January 2024 were enrolled. The alterations in gastrointestinal peptide hormones, including insulin (INS), leptin (Lep), glucagon-like peptide-1 (GLP-1), and ghrelin (GHR), before and after surgery were measured. Subsequently, a 6-month follow-up was conducted. Patients with weight regain were identified, and the predictive value of gastrointestinal peptide hormones for weight regain was analyzed. Logistic regression was then employed to analyze the related factors affecting weight regain.Results: Following the surgical procedure, a significant increase was observed in the levels of INS, Lep, and GLP, accompanied by a notable decrease in GHR levels among the patients (P < 0.05). During the follow-up period, 32 patients experienced weight regain. The receiver operating characteristic (ROC) curve analysis demonstrated that gastrointestinal peptide hormones exhibited outstanding predictive capabilities for postoperative weight regain. Moreover, through statistical analysis, it was determined that unfavorable dietary habits, lack of regular exercise, trace element deficiencies, and negative emotional states were independent risk factors influencing weight regain following LSG (P < 0.05).Conclusion: There is a close correlation between gastrointestinal peptide hormones and post-LSG weight alterations in patients with OHS.